ISOLASI SENYAWA ALKALOID DARI KULIT BATANG Dehaasia lancifolia BL. Ridl - Hasnirwan, Hasnirwan; Arbain, Dayar; Effendy, Harry Abrir (Jurnal Riset Kimia, 2010)
ABSTRACT Dehaasia lancifolia plant from family of Lauraceae and base on the phytochemical survey in Malaysia and West Sumatera containing alkaloid compounds. The alkaloid compounds containing in Dehaasia lancifolia BL. Ridl has not been isolated and from chemotaxonomy aproximation gave an indication that alkaloid structure not quite difference with one of Phoebe genus of the same family wich has been isolated. The isolated alkaloid compound was obtained in amorf solid phase and yellowish colored in relatively high concentration. The bromide salt of this compound melt at 261°-264°C. UV spectrum indicated the maximum absorbtion band at wavelength 282 and 204 nm wich indicated the chromophoric group of tetrahydroquinoline. IR spectrum shown an absorbtion band at: 3550 cm-1 (stretching C-N), 3030 cm-1 (C-H aromatic), 2930 cm-1 (-CH2- stretching), 2860 (CH aliphatic stretching), 1660-1600 cm-1 (C=C aromatic), 1530 cm-1 (C=N aromatic), 1070 cm-1 (C-O-C stretching) and brommide salt shown an absorbtion band at 2680 cm-1 (>N+-H stretching) and without OH group in this molecule Keywords: dehaasia lancifolia BL. Ridl, alkaloid, spectrophotometer UV and IR